Personality and Information Gathering in Free-Ranging Great Tits - van Overveld, Thijs (Public Library of Science, 2013)
One aspect of animal personality that has been well described in captivity, but received only little attention in studies in the wild, is that personality types may vary in their behavioural flexibility towards environmental changes. A fundamental factor underlying such differences is believed to be the degree to which individual behavior is guided by environmental stimuli. We tested this hypothesis in the wild using free-ranging great tits. Personality variation was quantified using exploratory behaviour in a novel environment, which has previously been shown to be repeatable and correlated with other behaviours in this and other populations of the same species. By temporarily removing food at feeding stations we examined whether birds with different personality differed in returning to visit empty feeders as this may provide information on how birds continue to sample their environment after a sudden change in conditions. In two summer experiments, we found that fast-exploring juveniles visited empty feeders less often compared to slow-exploring juveniles. In winter, sampling behaviour was sex dependent but not related to personality. In both seasons, we found that birds who sampled empty feeders more often were more likely to rediscover food after we again re-baited the feeding stations, but there was no effect of personality. Our results show that personality types may indeed differ in ways of collecting environmental information, which is consistent with the view of personalities as different styles of coping with environmental changes. The adaptive value of these alternative behavioural tactics, however, needs to be further explored.